The Application of Cleanliness, Health, Safety (CHS) on Homestay in the New Normal Era - Wijoyo, Tuwuh Adhistyo; Maria, Aletta Dewi; Octafian, Ray (International Journal Labs, 2021)
One of the countries that has also been affected by this pandemic is Indonesia. Having a large area, of course, makes the Indonesian government expected to move quickly in dealing with the pandemic that has caused turmoil in several sectors of the Indonesian economy, one of which is the tourism sector. The policies implemented by the government brought the community into a period called the New Normal era. Tourist villages are expected to be able to start opening tourism activities, one of which is homestays by implementing strict health protocol which are summarized in the Cleanliness, Health, and Safety (CHS) program, even by the CHS ministry this is used as a new competency in the hope of increasing public trust in the new normal era. This study aims to discover the implementation of CHS in homestays in Sikasur Tourism Village during the New Normal period. This study uses a naturalistic method. This method is used to research in a natural place. There is an answer finding in this study related to the application of CHS to homestays in this new normal period, namely the shadow of fear of the spread of covid must be eliminated through the readiness of each tourism actor, continue to obey the health protocols during the process of building tourism and eliminate first looking for as much profit as possible. Which actually worsened the situation and harmed many parties.